On the interpretation of results from small punch creep tests - Hyde, T H.; Stoyanov, M; Sun, Wei; Hyde, Christopher J. (SAGE, 2010)
The small punch creep testing method is highly complex and involves interactions between a number of non-linear processes. The deformed shapes that are produced from such tests are related to the punch and specimen dimensions and to the elastic, plastic, and creep behaviour of the test material, under contact and large deformation conditions, at elevated temperature. Owing to its complex nature, it is difficult to interpret the small punch test creep data in relation to the corresponding uniaxial creep behaviour of the material. One of the aims of this paper is to identify the important characteristics of the creep deformation resulting from ‘localized’ deformations and from the ‘overall’ deformation of the specimen. Following this, the results of approximate analytical and detailed finite element analyses of small punch tests are investigated. It is shown that the regions of the uniaxial creep test curves dominated by primary, secondary, and tertiary creep are not those that are immediately apparent from the displacement versus time records produced during a small punch test. On the basis of the interpretation of the finite element results presented, a method based on a reference stress approach is proposed for interpreting the results of small punch test experimental data. Future work planned for the interpretation of small punch tests data is briefly addressed.